Growth study of DF-1 cell line in microcarrier bioreactor - Arifin, Mohd Azmir; Mel, Maizirwan; Ahmad Raus, Raha; S. H., Sharifah; Ideris, Aini (2008)
Animal cell culture is fundamental in the manufacturing of many biological products. Biological products produced in animal cell cultures include vaccines, enzymes, hormones, antibodies and anticancer agents. However majority of animal cells is anchorage-dependent and requires attachment to a surface for their growth. Microcarrier is a small bead used to provide surface for the culture of anchorage-dependent animal cells. Microcarrier culture has very large surface area to volume ratio, thus able to produce larger number of cells when compared to conventional monolayer cultures which uses multiple glass or plastic bottles. This research was carried out mainly to study the growth performance of DF-1 cell culture by using microcarriers in a 1-L litre stirred tank bioreactor and compares it with conventional monolayer cultures grown in T-flasks bioreactor. At the end of the study it has been found that the maximum viable cell concentration achieved by the microcarrier culture was 1.315 × 106 cells/ml which was higher than maximum viable cell concentration achieved by the cell culture in T-flasks which was 1.25 × 106 cells/ml.